Fipronil Alters the Circadian Clock-controlled Protein Gene and the Action of Juvenile Hormone in Bees, Apis mellifera L. - Aline Astolfi; Samir Moura Kadri; Isabella Cristina de C. Lippi; Daniel Nicodemo; Ricardo de Oliveira Orsi (Sociobiology)
Apis mellifera bees are considered efficient pollinators of wild plants and crops; however, during the food search, foraging bees can become contaminated with persistent insecticides in the environment, which harms bees' health lethally or gradually over time. Gene expression analysis is a way of investigating the changes caused in the body by pesticide contamination. Using the transcriptome, the present study investigated the effect of fipronil on the gene expression of bees in the forage phase contaminated by ingestion for 4 hours. The insecticide fipronil, at an environmentally relevant dose (2.5 ppb), downregulated the transcription of the circadian clock-controlled protein gene, a gene encoding transport proteins controlled by the circadian rhythm, suggesting that exposure to fipronil can affect the circulation of juvenile hormone in the body and, consequently, harm the development of the colony.